Night Watch Nochnoi Dozor - Maximov, Anatoly; Ernst, Konstantin, 1961-; Bekmambetov, Timur, 1961-; Luk'?i?anenko, Sergei; Kalogridis, Laeta; Khabenskii, Konstantin, 1972-; Menshov, Vladimir; Zolotukhin, Valerii; Poteyenko, Yuri; Fox Searchlight Pictures; Channel One Russia; Kinokompani?i?a Tabbak; et al. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2006)
The forces of Light and Darkness have co-existed in a delicate balance for hundreds of years...until now. Even as the Night Watch polices the Dark Others--among them vampires, witches and shape-shifters--a chain of mysterious events triggers a dreaded, age-old prophecy: An immortal with special powers will come to switch sides, shattering the balance and unleashing an apocalyptic war unlike any the world has ever known
Based on the novel by Sergie Lukyanenko
Videodisc release of the 2004 motion picture
Special features: Side A Widescreen English version, Side B Widescreen Russian version ; Extended ending with optional commentary by co-writer/ director Timur Bekmambetov ; Subtitled commentary (in English, French or Spanish) by renowned novelist Sergei Lukyanenko ; Sneak previews of upcoming Night Watch sequels
Director of photography, Sergei Trofimov ; editor, Dmitri Kiselev ; music by Yuri Poteyenko
Konstantin Khabensky, Vladimir Menshov, Valery Zolotukhin, Maria Poroshina, Galina Tunina
Konstantin Khabensky
Keywords: Feature films